Ekspresi Enzim Metabolisme Vitamin D Pada Sistem Reproduksi Pria - Syauqy, Ahmad (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2015)
ABSTRACT Nowadays moleculer biology is developed. The scientist try to make a mapping of proteins that exist in male reproduction. It is supposed to know fertility factor for advance in moleculer way so that it can be used as the information to solve the infertility cases in male. One of the protein that is identificated in male reproduction system is enzyms that used in metabolism vitamin d. Those enzyms is known can be found in organ that is used in metabolism vitamin D, they are liver and kidney. On liver, enzym 25-d- hidroksilade exist and it is used to activate vitamin D. Meanwhile, on kidney enzym 24-hydroksilase exist, it is used to inactivate vitamin D. All of the enzyms are used in activate and inactivate vitamin D are also use in male reproduction tract and so do sprem with variation level of expression. It show that vitamin D is also take an important role in male fertility. The use of vitaminD specificly is not much revealed yet in male reproduction system. The use of vitaminD that has been revealed was sperm capacity, sperm motility and to increase the resistancy of sperm. Â  Keyword : enzym,vitamin D,male reproduction